Unequal Distribution of Health Workers in South Kalimantan: Implications for Policy and Budget Planning - Noor, Meitria Syahadatina; Nurhidayah, Nurhidayah; Sudaryanti, Dwiyani; Shaddiq, Syahrial (Yayasan Sembilan Pemuda Indonesia, 2025)
Health workforce data is an essential foundation for planning and evaluating a region’s health system. Analysis of the distribution and composition of health human resources (HR) in South Kalimantan reveals patterns of spatial inequality and the dominance of certain professions. This reseacrh aims to explore the implications of HR data on the quality of health program planning and budgeting at the provincial and district/city levels. Results indicate that the concentration of human resources in urban areas, the dominance of nursing and midwifery professions, and the shortage of several other HR professionals require targeted policy interventions. Contribution the research include strengthening equitable distribution policies, investing in education and training, and needs-based budgeting to achieve optimal coverage and quality of health services.